No, Band84 isn't right. I think that in this case the index -1 means the inverse function.
One way of doing this is to write the function as
y = 2x/(1-x),
then get the inverse by swapping x and y:
x = 2y/(1-y)
and then make y the subject of this equation.
You should get
y = x/(2+x)
and so
(h^-1)(x) = x/(2+x)
I see a couple of other people submitted this solution while I was typing it out. Another way of doing it is this:
The expression can be written as
(2(x-1) + 2)/(1-x)
= -2 + 2/(1-x)
In words this can be stated as
Start with x
Multiply by -1
Add 1 [At this stage we have 1-x]
Invert
Multiply by 2
Subtract 2.
To find the inverse function, do the opposites of these operations in the reverse order, thus:
Add 2, giving x+2
Divide by 2, giving (x+2)/2
Invert, giving 2/(x+2)
Subtract 1, giving 2/(x+2) -1
Multiply by -1, giving 1 - 2/(x+2)
and of course this last expression simplifies to
x/(x+2)
2006-10-19 17:22:13
·
answer #1
·
answered by Hy 7
·
0⤊
0⤋
h^-1(x)=x/(2+x)
2006-10-19 17:19:06
·
answer #2
·
answered by masmasac 2
·
0⤊
0⤋
Given h(x)=2x/(1-x)
let h^-1(x)=y
=> x=h(y)
=> x=2y/(1-y),making 'y' as subject, we get
y=x/(x+2)
therefore, h^-1(x)=x/(x+2)
NOTE: As one of the answers given,h^-1(x) is not equal to 1/h(x).
2006-10-19 17:42:54
·
answer #3
·
answered by ashok r 1
·
0⤊
0⤋
start up by way of removing the parentheses (distributive assets): 5x+12-4x-6-2x-5+2x=a million+1x combine like words (upload constants with different constants and multiples of the variable at the same time): (5x-4x-2x+2x)+(12-6-5)=a million+1x 1x+a million=a million+1x in case then you definitely resolve this for x, you will discover that the x words disappear: 0=0 this implies you may plug in any real value for x and function the equation be real.
2016-12-08 17:48:04
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
h^-1 (x) = 1/h(x) = (1-x)/2x
2006-10-19 17:14:07
·
answer #5
·
answered by bandl84 3
·
0⤊
0⤋
to find the inverse of function try this
y=2x/(1-x)
and solve for x
(1-x)y=2x
y-xy=2x
y=2x+xy
y=x(2+y)
y/(2+y)=x
h(x)= x/(2+x)
2006-10-19 17:19:49
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
y = 2x/(1-x)
y-xy = 2x
y = 2x+xy = x(y+2)
x = y/(y+2)
inv(h(x)) = x/(x+2)
2006-10-19 17:34:33
·
answer #7
·
answered by Helmut 7
·
0⤊
0⤋
h(x) = (2x)/(1 - x)
y = (2x)/(1 - x)
x = (2y)/(1 - y)
x - xy = 2y
-xy - 2y = -x
-(xy + 2y) = -x
xy + 2y = x
y(x + 2) = x
y = x/(x + 2)
ANS :
h^-1(x) = x/(x + 2)
2006-10-19 18:26:35
·
answer #8
·
answered by Sherman81 6
·
0⤊
0⤋